Comparison of bias correction methods to enhance CHIRP rainfall estimates for improved streamflow simulation at Ziway-Shalla Catchment, Ethiopia - Beyene, T. L.; Haile, Alemseged Tamiru; Goshime, D. W.; Birhan, S. T. (Elsevier, 2025)
Study region: Ziway-Shalla Catchment, Rift Valley Basin, Ethiopia.